Investigation Of The Effects Of Laser Micro-Texturing On The Cellular Response Of Silicon Surfaces - Oyatogun, G.M.; Imasogie, B.I.; Soboyejo, W.O.; Abere, V.D.; Oyatogun, A.O.; Popoola, A.P.I. (Ife Journal of Technology, 2019)
This study investigated the effects of laser micro-texturing on the interaction of silicon with cancer cells. This was with a view to improve the biocompatibility of silicon and to enhance its biomedical applications. The modification of silicon surface was carried out by the fabrication of microgrooves of different spacing on its surface using laser nano-second technique. Surface characterizations of the modified and unmodified samples were carried out using Scanning Electron Microscopy (SEM). Human osteosarcoma cells were cultured on the surfaces to study the effects of this modification process on cellular response. Optical and immunofluorescent microscopy were used to study the morphology and adsorption of cells on the different cultured samples. Micro-texturing was found to encourage the spreading of cells, with definite orientation and alignment along the groove ridges, thereby improving its biocompatibility. Increasing grooves spacing was found to enhance the adsorption and proliferation of cancer cells. This study therefore facilitates the development of substrates with improved biocompatibility for the design and fabrication of biomedical devices for cancer diagnosis and treatment.